1998
DOI: 10.1161/01.atv.18.2.152
|View full text |Cite
|
Sign up to set email alerts
|

The PAI-1 Gene Locus 4G/5G Polymorphism Is Associated With a Family History of Coronary Artery Disease

Abstract: Abstract-A family history of ischemic events is a major determinant of coronary artery disease (CAD). Plasma levels of plasminogen activator inhibitor 1 (PAI-1) modulate this risk. A deletion/insertion polymorphism within the PAI-1 locus (4G/5G) affects the expression of this gene. We investigated the relationship between the PAI-1 4G/5G polymorphism in 1179 healthy employees of our institution and the occurrence of CAD in their first-degree relatives. A family history of documented ischemic coronary disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 36 publications
7
68
0
5
Order By: Relevance
“…6 -8 We have previously found that the 4G/4G gene variant of the plasminogen activator inhibitor-1 (PAI-1) gene is associated with a history of coronary artery disease in a first-degree relative. 9 Raised concentrations of C-reactive protein (CRP) have been found to predict recurrent ischemia, myocardial infarction, and sudden death among patients with multiple risk factors for coronary artery disease and angina pectoris. 10 -12 In the ECAT study, raised levels of CRP at baseline consistently predicted myocardial infarction or sudden death over the 3 years of follow-up.…”
mentioning
confidence: 99%
“…6 -8 We have previously found that the 4G/4G gene variant of the plasminogen activator inhibitor-1 (PAI-1) gene is associated with a history of coronary artery disease in a first-degree relative. 9 Raised concentrations of C-reactive protein (CRP) have been found to predict recurrent ischemia, myocardial infarction, and sudden death among patients with multiple risk factors for coronary artery disease and angina pectoris. 10 -12 In the ECAT study, raised levels of CRP at baseline consistently predicted myocardial infarction or sudden death over the 3 years of follow-up.…”
mentioning
confidence: 99%
“…In relation to the rest of polymorphisms, Margaglione et al [28] in a cohort of 1,179 healthy employees found that the 4G/4G carriers exhibited a more frequent family history of CAD, supporting the hypothesis that the 4G variant was a transmissible coronary risk factor. However, Panahloo et al [29] found no evidence that subjects with the 4G/4G polymorphism had higher PAI-1 levels on admission or 6 months after MI.…”
Section: Gpiiia No-a1a1 (A1a2+a2a2) Gpiiia A1a1mentioning
confidence: 88%
“…U estalost PAI-1 4G/5G genske varijante varira zavisno od etni ke pripadnosti (17)(18)(19)(20)(21)(22). Frekvenca ove genske varijante odre ivana je za veliki broj populacija, ali do sada nema objavljenih podataka za srpsku populaciju.…”
Section: Uvodunclassified
“…The prevalence of PAI-1 4G/5G gene variant varies depending on ethnicity (17)(18)(19)(20)(21)(22). The frequency of this gene variant was determined for a number of populations, but there is no data observed for Serbian population.…”
Section: Introductionmentioning
confidence: 99%